Biocompatible fluorescent probe for detecting mitochondrial alkaline phosphatase activity in live cells - Khatun S.; Biswas S.; Mahanta A.K.; Joseph M.M.; Vidyalekshmi M.S.; Podder A.; Maiti P.; Maiti K.K.; Bhuniya S. (My University, 2025)
Alkaline phosphatase (ALP) is an enzyme that actively plays a significant role in the various metabolic processes by transferring a phosphate group to the protein, nucleic acid, etc. The elevated level of ALP in blood plasma is the hallmark of inflammation/cancer. The hyperactive mitochondria in cancer cells produce an excess of ATP to fulfill the high energy demand. Thus, we have developed a fluorescent probe Mito-Phos for ALP, which can detect phosphatase expression in mitochondria in live cells. The probe Mito-Phos has shown ~15-fold fluorescence intensity increments at 450 nm in the presence of 500 ng/mL of ALP. It takes about 60 min to consume the whole amount of ALP (500 ng/mL) in physiological buffer saline. It can selectively react with ALP even in the presence of other probable cellular reactive components. It is highly biocompatible and nontoxic to the live cells. It has shown ALP expression in a dose-dependent manner by providing concomitant fluorescence images in the blue-channel region. It has localized exclusively in the mitochondria in live cells. The probe Mito-Phos is highly biocompatible with the ability to assess ALP expression in mitochondria in live cells. © 2020 Elsevier B.V.